Collaborative innovation and policy support: the emergence of trilateral networks. Issue 34 (20th July 2020) - Song, Yang; Elsner, Wolfram; Zhang, Zhiyuan; Berger, Ron
ABSTRACT: The present article models the critical factors for a successful and evolutionarily stable National System of Innovation. We simulate a model, against the background of increasingly complex technologies, in a national process of agents' interactions with social-dilemma characteristics. In particular, the articleinvestigates the emergence of a trilateral collaborative innovation alliance among 'enterprise', 'university' and 'government'. We apply a tripartite evolutionary game with a replication process and explore the role and options of the public policy agent to support collaboration on innovation. We find that some policy mix, in particular, a combination of (1) public rewards for cooperation, (2) public punishment for non-cooperation and (3) settings of public cost controls and tax income from innovation, can promote broad and sustainable innovation alliances. For instance, threats of strong punishment, even with low public rewards for cooperation, may promote the formation of a collaborative innovation alliance. We run some sensitivity analyses of the results through parametric variation of two critical factors of the model, knowledge spillover and output elasticity of knowledge input. We find some qualifications for the velocity of the process.